Increasing the difficulty of elementary school students in science learning media - jiah, Sujiyah (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
Media is one of the most important tools for learning activities, the right media will support teaching and learning activities that take place in class. The media is an intermediary / liaison between teachers and students. Images can be used as educational media and have educational values for students that enable efficient learning of student participants related to the use of image media in science learning in elementary schools. But in fact sometimes teachers have not been able to use appropriate learning media in classroom learning activities.Learning achievement is a measure of a person's level of success in something, a person's achievement can be seen based on the score obtained in completing exam questions related to the material being pursued. Each learning course expects maximum learning outcomes, but in reality there are still students who get a science score below the KKM